1976
DOI: 10.1113/jphysiol.1976.sp011607
|View full text |Cite
|
Sign up to set email alerts
|

On the receptors which mediate the hyperpolarization of salivary gland cells of Nauphoeta cinerea Olivier.

Abstract: SUMMARY1. The actions of sympathomimetics and of catecholamine antagonists have been investigated on the membrane potential and responses to nerve stimulation of acinar cells of the salivary gland of Nauphoeta cinerea Olivier.2. Hyperpolarizations such as those evoked by nerve stimulation and by low concentrations of adrenaline, noradrenaline and dopamine were not produced by the a-agonists amidephrine and methoxamine. Isoprenaline was active, but only in concentrations above 100 /M.3. Tyramine, an indirectly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Interestingly, the electrical but not the secretory response could be blocked by the ergoline derivative ergometrine (Ginsborg et al, 1976a;Bowser-Riley et al, 1978), which is not only a DA-receptor antagonist (Ascher, 1972), but also a potent agonist at certain mammalian 5-HT-receptor subtypes (Brazenor and Angus, 1982;Bai et al, 2004). These pharmacological results support the hypothesis that at least two classes of aminergic receptors are expressed on the salivary gland of Nauphoeta (House, 1980).…”
Section: +supporting
confidence: 55%
“…Interestingly, the electrical but not the secretory response could be blocked by the ergoline derivative ergometrine (Ginsborg et al, 1976a;Bowser-Riley et al, 1978), which is not only a DA-receptor antagonist (Ascher, 1972), but also a potent agonist at certain mammalian 5-HT-receptor subtypes (Brazenor and Angus, 1982;Bai et al, 2004). These pharmacological results support the hypothesis that at least two classes of aminergic receptors are expressed on the salivary gland of Nauphoeta (House, 1980).…”
Section: +supporting
confidence: 55%
“…Secondly, the effects of dopamine and ADTN were not antagonized by haloperidol (10 gM), methysergide (10 gM), fluphenazine (1 gM) or a-flupenthixol (1 gM). (These are potent antagonists of dopamine at other sites: Seeman, Lau Wong, Tedesco & Wong, 1975;Dray, Gonye & Oakley, 1976;Burt, Creese & Snyder, 1976;Ginsborg, House & Silinsky, 1976.) Control responses to phenylephrine or noradrenaline were also unaffected by these drugs.…”
Section: Dopamine Receptors?mentioning
confidence: 99%
“…Finally, phentolamine reversibly blocked the secretory response to exogenous cyclic AMP or IBMX. Previously it had been shown that phentolamine is a competitive antagonist of the dopamine-evoked hyperpolarization of acinar cells and fluid secretion by the gland (Ginsborg, House & Silinsky, 1976;Bowser-Riley, et al 1978). Now it is also evident that phentolamine might act within the acinar cells at a stage after cyclic AMP synthesis.…”
Section: Cyclic Amp As a Mediatormentioning
confidence: 99%